2013
DOI: 10.1093/ntr/ntt187
|View full text |Cite
|
Sign up to set email alerts
|

Classifying a Smoker Scale in Adult Daily and Nondaily Smokers

Abstract: introduction: Smoker identity, or the strength of beliefs about oneself as a smoker, is a robust marker of smoking behavior. However, many nondaily smokers do not identify as smokers, underestimating their risk for tobacco-related disease and resulting in missed intervention opportunities. Assessing underlying beliefs about characteristics used to classify smokers may help explain the discrepancy between smoking behavior and smoker identity. This study examines the factor structure, reliability, and validity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
2
17
0
1
Order By: Relevance
“…Whereas many studies on the subset of nondaily smokers who are primarily social smokers often focus on young adults, our study was restricted to participants 25 years of age or older. This explanation is consistent with another study which found differences in smokingrelated characteristics between a college sample and a sample of older, more established smokers (Pulvers et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Whereas many studies on the subset of nondaily smokers who are primarily social smokers often focus on young adults, our study was restricted to participants 25 years of age or older. This explanation is consistent with another study which found differences in smokingrelated characteristics between a college sample and a sample of older, more established smokers (Pulvers et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Quotas for the number of participants by smoking level were 1,200 for nondaily smokers, 600 for light daily smokers, and 600 for moderate to heavy daily smokers. The final study sample consisted of 2,376 participants, which is described in detail in Pulvers et al (2013).…”
Section: Participantsmentioning
confidence: 99%
“…This is consistent with national prevalence data and reinforces the need for ongoing treatment studies with this growing subpopulation of smokers [1]. However, almost half of NDS who met our initial screening criteria did not keep their in-person appointment, possibly reflecting lower identity as a smoker and ambivalence about quitting smoking among this group [65]. As a result, we screened 2,528 people in order to randomize 278 NDS.…”
Section: Discussionsupporting
confidence: 74%
“…As displayed in Table 3, the median age of the male patient was 41 years (interquartile range 37-45) and the median age of the female partner was 37 years (34-41). The median duration of infertility before treatment was 23 months (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Furthermore, information on the health risk factor smoking was present in 38 patients, of whom 11 (29%) were smokers (Table 3).…”
Section: Patients' Characteristicsmentioning
confidence: 99%
“…Regarding the smoking intensity we had information on 5 patients. Of these, 3 out of 5 patients (60%) were non-daily smokers (> 1 cigarette per day on 4-24 days in the past 30 days) and 2 out of 5 patients (40%) were light daily smokers (≤10 cigarettes per day), none of the patients was a moderate to heavy daily smoker (> 10 cigarettes per day) [12]. The median testicular volume that was measured via ultrasound analysis was 12 mL (8-20), Table 3.…”
Section: Patients' Characteristicsmentioning
confidence: 99%